Kesulitan Menyimak dan Strategi Mahasiswa dalam Memahami Bagian Listening Comprehension pada Tes TOEIC - Lina Meilinda; Siti Yuliah (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
This study is aimed to identify the difficulties to comprehend listening activities experienced by students and their strategies in understanding Listening Comprehension section of TOEIC test. Descriptive qualitative method was employed to find out and analyze the difficulties and strategies the students implemented. The research was carried out at English Department of Politeknik Negeri Bandung with the population of the third semester students in Academic Year 2017/2018. There were 22 students as the subject in this study. Data were collected by questionnaires and interview to confirm students’ answers. The results showed that the major problems encountered by students were unfamiliar vocabulary, accents of the speaker, speed of speech, lack of concentration, and quality of recorded materials. Listening strategies implemented by students were mostly metacognitive strategy since in this strategy they obtain the awareness of the materials they are listening to in a more cautious way. This method is about the ways of planning, monitoring and assessing the collected information from the listening section the same as pre listening activities. Students applying metacognitive strategies have the benefits such as they can use appropriate learning strategy to master learning materials; they comprehend learning materials more quickly and integrate the knowledge seriously; they put themselves to be loyal receivers and can be properly adaptable to all conditions; they have high confidences in themselves to get help when needed from their peers, teachers, or family; they pay attention to the materials and assess themselves as to how to be successful learners; and they properly deal with the problems in doing their task. Keywords: Students’ Difficulties, Listening Comprehension, Listening Strategies